2018
DOI: 10.3390/nu10020168
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Magnesium and Cardiovascular Disease: A Review with Emphasis in Epidemiological Studies

Abstract: Magnesium (Mg) is an essential dietary element for humans involved in key biological processes. A growing body of evidence from epidemiological studies, randomized controlled trials (RCTs) and meta-analyses have indicated inverse associations between Mg intake and cardiovascular diseases (CVD). The present review aims to summarize recent scientific evidence on the topic, with a focus on data from epidemiological studies assessing the associations between Mg intake and major cardiovascular (CV) risk factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 104 publications
(152 reference statements)
1
88
1
5
Order By: Relevance
“…Although intervention studies with Mg supplements and under controlled experimental conditions may provide a high level of scientific evidence, these studies also have limitations related with small sample size and special population characteristics, and so it is necessary to obtain additional evidence from other studies, even though they be of an observational nature. Among those observational studies, much research has been undertaken on whether there exists a relationship between magnesium contribution through dietary food and different cardiovascular risk factors, diabetes and cardiovascular diseases [38]. Thus, some studies have reported inverse associations between dietary magnesium intake and body mass index (BMI) or obesity [39,40], blood pressure [40,41], total cholesterol/LDL-cholesterol concentrations [42], and fasting glucose or type-2 diabetes [41,43,44], but the overall consistency for some of these factors is still low.…”
Section: Introductionmentioning
confidence: 99%
“…Although intervention studies with Mg supplements and under controlled experimental conditions may provide a high level of scientific evidence, these studies also have limitations related with small sample size and special population characteristics, and so it is necessary to obtain additional evidence from other studies, even though they be of an observational nature. Among those observational studies, much research has been undertaken on whether there exists a relationship between magnesium contribution through dietary food and different cardiovascular risk factors, diabetes and cardiovascular diseases [38]. Thus, some studies have reported inverse associations between dietary magnesium intake and body mass index (BMI) or obesity [39,40], blood pressure [40,41], total cholesterol/LDL-cholesterol concentrations [42], and fasting glucose or type-2 diabetes [41,43,44], but the overall consistency for some of these factors is still low.…”
Section: Introductionmentioning
confidence: 99%
“…Großangelegte Metaanalysen der letzten Jahre zeigten zunächst eine inverse Korrelation zwischen der über die Nahrung zugeführten Menge an Magnesium und dem Risiko für kardiovaskuläre Erkrankungen [9].…”
Section: Magnesiumunclassified
“…Dieser Befund konnte jedoch in späteren Metaanalysen nicht mehr aufgezeigt werden[5]. Obwohl die Menge an zugeführtem Magnesium kaum mit der Plasmakonzentration korreliert, konnte die Magnesiumkonzentration im Serum mit einem verringerten kardiovaskulären Risiko assoziiert werden[9][11].…”
unclassified
“…Magnesium (Mg) is an essential nutrient for plants as well as animals. In humans, a low dietary Mg intake is associated with cardiovascular disease and its risk factors including hypertension as well as metabolic syndrome and type 2 diabetes among other chronic diseases (Ma et al 1995;Volpe 2012;Zhang et al 2012;Del Gobbo et al 2013;Kass and Sullivan 2016;Zhang et al 2016;Verma and Garg 2017;Rosique-Esteban et al 2018). Plant source foods are the source of most human Mg intake, especially cereal grains, green vegetables, nuts and pulses (Nielsen 2015), with grains supplying the vast majority of dietary Mg to humans (EFSA Panel on Dietetic Products Nutrition and Allergies 2015; Kumssa et al 2015).…”
Section: Introductionmentioning
confidence: 99%